2008
DOI: 10.1007/s00466-007-0238-y
|View full text |Cite
|
Sign up to set email alerts
|

Coupled FEM and BEM code for simulating acoustically excited bubbles near deformable structures

Abstract: An understanding of biotissue-bubble interactions and the stresses induced in the tissue is needed to identify potential mechanisms of tissue damage, such as vessel rupture, by acoustically excited bubbles. Interactions between acoustically excited bubbles and nearby rigid structures have been studied effectively using the boundary element method. However, if the nearby structure is a biotissue, structure deformations will affect the bubble response. In this paper a coupled finite element and boundary element … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…Any method that can calculate the radius as a function of time of an oscillating bubble can be input. Particularly, a method that accounts for the elasticity of the vessel wall, such as that of Miao and Gracewski[13] may be more appropriate. The current models of bubbles within tubes (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Any method that can calculate the radius as a function of time of an oscillating bubble can be input. Particularly, a method that accounts for the elasticity of the vessel wall, such as that of Miao and Gracewski[13] may be more appropriate. The current models of bubbles within tubes (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies focused on comparing the circumferential stress to the tensile strength of the vessel wall to predict the damage threshold. Under ultrasound excitation with PNP 0.2 MPa and center frequency 1 MHz, the maximum hoop stress exceeded 1.5 MPa assuming the vessel wall elasticity 5 MPa [11,12]. However, it is possible that the rapid compression stress during bubble collapse plays important role in the microvessel wall in ultrasound field.…”
Section: The Effect Of Ultrasound Pnp Valuesmentioning
confidence: 99%
“…The mechanical property of the vessel wall was assumed to be linear elastic material in most studies [10][11][12]. However, Fung's experimental study showed that the stressstrain relationship was nonlinear when a torsion test was made on the mesentery.…”
Section: The Effect Of Ultrasound Pnp Valuesmentioning
confidence: 99%
See 1 more Smart Citation
“…Their simulation went on after the jets contacted, which showed that a toroidal bubble formed at the end of the collapse, afterwards a ring-shaped jet was generated pointing towards the tube wall. On the bubble collapse in an elastic tube, a coupled FEM and BEM code for simulation was developed by Miao [14], describing the typical bubble-tube interactions and stresses. Coralic [15] studied shock-induced collapse of a bubble inside a deformable vessel, whose results showed that a 40 MPa shockwave to collapse the bubble generated a vessel wall pressure of almost 450 MPa, inducing an invagination of nearly 50% of the initial vessel radius on a 10 ns timescale.…”
Section: Introductionmentioning
confidence: 99%